REVITALISASI PERAN PROFETIK PESANTREN DALAM MEMBENDUNG RADIKALISME AGAMA - Mujib Ridlwan (Al Hikmah: Jurnal Studi Keislaman, 2013)
Strong religious spirit is not accompanied by a proper understanding of religion will cause damage and madharat to themselves and others. Therefore, in this case religious education schools have a very important role to stem the madharat as violence, either violence motivated by religious sentiments, class, and regional sentiment. Unfortunately the role of pesantren which was originally to be a central and trusted by the community as well as educational institutions to study religion, now is in decline due to a number of things, such as education schools judged to be able to answer the challenges of the times for the future of their children. This is the work of the scholars in order to reinstate the schools function as a reference every issue surrounding communities. Prophetic role of schools should be re-built for the prosperity of the people of this country and build social justice for all people.